Toward a More Comprehensive Concept of Successful Aging: Disability and Care Needs. (1st March 2017) - Tesch-Römer, Clemens; Wahl, Hans-Werner
Abstract: Rowe and Kahn's model of Successful Aging 2.0 argues that changing environmental settings, societal policies, and individual life styles will lead to a significant extension of healthy life years. Recent epidemiological research, however, confirms the dilemma that the ongoing extension of life expectancy prolongs not only the years in good health but also those in poor health. We see it as a major limitation that Rowe and Kahn's model is not able to cover the emerging linkage between increasing life expectation and aging with disability and care needs. Therefore, we suggest a set of propositions towards a more comprehensive model of successful aging which captures desirable living situations including for those who grow old with disabilities and care needs. We describe individual, environmental, and care related strategies and resources for autonomy and quality of life when facing disabilities and care needs in late life, putting emphasis on inter-individual differences and social inequality. We argue that expanding the traditional concept of successful aging to aging with disabilities and care needs serves not to undermine, but rather to anchor the concept in aging science and in public perception.